Empowerment of Former Women Migrant Workers Based on Social Capital and Local Economic Potential - Wafiroh, Nurotul; Setiana, Dafid Slamet (West Science Social and Humanities Studies, 2024)
This article discusses efforts to empower women former migrant workers through an approach based on social capital and local economic potential. This research aims to identify effective empowerment strategies for women who have returned from working abroad, by utilizing their social networks and the economic resources available in their areas of origin. The research method used is descriptive qualitative with data collection through in-depth interviews, participatory observation and documentation. The research results show that social capital, such as individual and community networks, trust, and social norms, plays an important role in facilitating the process of reintegration and economic empowerment. In addition, utilizing local economic potential, such as micro and small businesses, agriculture and handicrafts, has been proven to make a significant contribution in improving the welfare and economic independence of women who are post-migrant workers. This article concludes that integrating social capital with local economic potential is an effective and sustainable strategy for empowering women as migrant workers.